2019
DOI: 10.1212/wnl.0000000000007945
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative MR neurography biomarkers in 5q-linked spinal muscular atrophy

Abstract: ObjectiveTo characterize and quantify peripheral nerve lesions and muscle degeneration in clinically, genetically, and electrophysiologically well-classified, nonpediatric patients with 5q-linked spinal muscular atrophy (SMA) by high-resolution magnetic resonance neurography (MRN).MethodsThirty-one adult patients with genetically confirmed 5q-linked SMA types II, IIIa, and IIIb and 31 age- and sex-matched healthy volunteers were prospectively investigated. All patients received neurologic, physiotherapeutic, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
47
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 29 publications
(49 citation statements)
references
References 41 publications
1
47
0
1
Order By: Relevance
“…Importantly, treatment response should not be based on the improvement of motor function alone, but focus on preventing all aspects of disease progression. This may include additional objective measurements of disease progression, like quantitative high-resolution muscle ultrasound or MRI of muscle and peripheral nerve to indicate early nerve tissue changes and to detect and measure the progression of muscular atrophy and nerve tissue changes in response to the treatment [34][35][36]. In addition, suitable questionnaires for patient-related outcomes have to be developed to assess the efficacy of future treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, treatment response should not be based on the improvement of motor function alone, but focus on preventing all aspects of disease progression. This may include additional objective measurements of disease progression, like quantitative high-resolution muscle ultrasound or MRI of muscle and peripheral nerve to indicate early nerve tissue changes and to detect and measure the progression of muscular atrophy and nerve tissue changes in response to the treatment [34][35][36]. In addition, suitable questionnaires for patient-related outcomes have to be developed to assess the efficacy of future treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, SMN-driving pharmacotherapies could be administered to SMA patients irrespective of their SMN2 copy number, with decisionmaking on the continuation of further treatment depending on individual clinical and biomarker responses [44]. In this context, quantitative imaging biomarkers such as MTR, T2 app or q [13] could be a valuable contribution. The relatively low number of patients in the present study limited our ability to significantly delineate differences in MTR (and/or CSA) between SMA 3a and 3b, even though a tendency towards lower MTR values was observed in the more severely affected SMA 3a patients.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we reported that high-resolution magnetic resonance neurography (MRN) [8][9][10][11][12] detects and quantifies peripheral nerve involvement in adults with SMA with high sensitivity [13]. We concluded that the two quantitative MRN markers apparent T2-relaxation time (T2 app ) and proton spin density (q) might serve as novel imaging biomarkers in SMA [13], but the macromolecular changes underlying alterations in T2 app and q are still not fully understood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Most imaging studies in SMA have focused on a qualitative appreciation of muscle, grading fat infiltration visually. [10][11][12][13][14][15][16][17][18][19][20] Quantitative MRI (qMRI) can complement qualitative evaluation of muscles and has shown promising results in other neuromuscular disorders, such as Duchenne muscular dystrophy (DMD) and limb girdle muscular dystrophies (LGMD). 21,22 Quantitative MRI in SMA has not been studied in detail.…”
Section: Introductionmentioning
confidence: 99%